Wood Micro-structural Studies of Indian Rutaceae Part V: Tribe Toddalieae - Bhardwaj, Nisha; Gupta, Sangeeta (Indian Forester, 2009)
The present study deals with the detailed wood anatomy of 3 Indian species belonging to 3 genera Acronychia Forst., Skimmia Thunb. and Vepris Comm. Of tribe Toddalieae under family Rutaceae. The results are summarized in the tables and identification key has been developed for the separation of 3 species of this tribe. Photomicrographs have been given for the diagnostic features. The woods of this tribe are used for making wheels, carts, helves, tool handles and agricultural implements. The wood anatomical parameters suggest that the tribe Toddalieae is a heterogeneous tribe characterized by diffuse porous woods. Skimmia have dendritic pattern in vessels. Growth ring distinct due to marginal bands of parenchyma; simple perforation plate; coalescent aperture; fibres non-septate. Almost all type of parenchyma represented in the species. Rays homogeneous to heterogeneous. Prismatic crystals and silica bodies present in fibre, rays and parenchyma of only one genus Vepris. Silica bodies are rarely present in rays in Acronychia. These three genera had not been reported in the Indian literature before present study. Since this is the last tribe of the family Rutaceae, a species identification key of the Indian species of the family Rutaceae has also been given along with tables illustrating both qualitative and quantitative features of this family.